Analysis of interest in using investment application platforms as a means of mutual fund investment among Gen Z and Gen Millennials - Gayatri, Putu Githa; Kurniawan, Yohannes (Edelweiss Applied Science and Technology, 2024)
This research aims to determine the factors that shape Gen Z and Gen Millennials’ interest in using platform investing in mutual fund applications. The factors tested as explanatory variables are Perceived Risk, Perceived Ease of Use, Perceived Usefulness, attitude towards Platform, Financial Literacy, Trust, and Technology Literacy. This research was conducted against the background of the low proportion of Gen Z and Gen Millennials who are investors in mutual funds, although in aggregate the number of investors in mutual funds tends to increase. This research was conducted on the Gen Z and Gen Millennial population registered with the Semi-Autonomous Body for the Capital Market Study Group, Faculty of Economics and Business, Udayana University, totaling 1,455 people. There were 306 respondents taken to represent the population through Purposive Sampling techniques. The results of analysis using SEM-PLS show that Perceived usefulness Impact on and Attitudes Towards Use. Perceived ease of use impacts Attitudes Toward Use and Gen Interest. Z. and Millennial Gen. Attitude Toward Usage impacts Gen Interest. Z. and Millennial Gen. Trust and Risk Perception Impact Attitudes Toward Use. Risk Perception has an impact on Attitudes Perceived Ease of Use. These results can provide implications for further discussion and development by further researchers, KSPM, and mutual fund application developers.